Histological Quantification of Angiogenesis after Focal Cerebral Infarction: A Systematic Review. (30th December 2013) - Leung, Wai Yin; Jensen, Matthew B.
Abstract : Ischemic stroke is a leading cause of disability, and current treatments to improve recovery are limited. Part of the natural recovery process after brain injury is angiogenesis. The formation of new blood vessels around the infarct appears to be important for restoration of adequate perfusion to allow for healing of brain tissue. Many potential restorative treatments may affect, and be affected by, angiogenesis, so accurate quantification of this outcome is needed. We performed a systematic review of histological methods to quantify angiogenesis after cerebral infarction. We found reports of the use of a variety of histological and general and immunostaining techniques in conjunction with a variety of analysis methods. We found no direct comparison studies and concluded that more research is needed to optimize the assessment of this important stroke outcome.